Smart Attendance Management System using Face Recognition - G, Gopalakrishnan; Alfy T, Jabin; V, Aadhithya; T, Manikandan; kumar T.K, Senthil (International Journal of Psychosocial Rehabilitation, 2020)
With the vast enhancements in telecommunication technologies, processing of audio and video has turned out to be an essential prerequisite. Human face, owing to its uniqueness, has become a more viable method of distinguishing one person from another. Hence, it has emerged to be one of the most popular and preferred systems for security and commercial applications. Attendance management by conventional means has proven to be tedious and time-consuming. Hence, the need for a more efficient means of smart attendance management has become prominent. This work proposes a new methodology in which the attendance of each individual student in a classroom is automatically updated in a database by analyzing their faces and comparing them with the predefined images by means of a face recognition module. The proposed system has achieved an accuracy of 93% to 95% for face recognition.